If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 2) + -3 = 2 Reorder the terms: 5(2 + x) + -3 = 2 (2 * 5 + x * 5) + -3 = 2 (10 + 5x) + -3 = 2 Reorder the terms: 10 + -3 + 5x = 2 Combine like terms: 10 + -3 = 7 7 + 5x = 2 Solving 7 + 5x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 5x = 2 + -7 Combine like terms: 7 + -7 = 0 0 + 5x = 2 + -7 5x = 2 + -7 Combine like terms: 2 + -7 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| 6-9*0=-21 | | 5(3x-1)=4(3x-2) | | 6-9*3=-21 | | -6-9*9=-21 | | 6-9*-5=-21 | | 5(x+4)-x=16 | | -91=-7(6+5) | | 3x-19=30 | | -91=-7(8+5) | | 5x-1+3x=11+4x | | -91=-7(-7+5) | | (2x-5)(2x-5)=(x-1)(x-1) | | -91=-71(-5+5) | | 200=49-u | | 88=8 | | -2.8x=-5.6 | | 8*9+7=39 | | 8*-2+7=39 | | 8*3+7=39 | | a(a-b)+2a=3+a(a-2) | | x^5-9x^4+26x^3-34x^2+25x-25=0 | | 8*-7+7=39 | | 18sint=0 | | 15-17=-2x | | 9x+5-3=2x+16 | | -63/7-1=7 | | 7/7-1=7 | | 56/7-1=7 | | 4+x=-11+9 | | 0/7-1 | | 0.10d+0.25q=8.65 | | 0/7-1=7 |